Academic Self-Efficacy and Academic Performance among Undergraduate Students in Relation to Gender and Streams of Education - Bhati, Khageswar; Baral, Rajashree; Meher, Venkateswar (Indonesian Journal of Contemporary Education, 2022)
In the study, an attempt has been made to investigate academic self-efficacy and academic performance of undergraduate students in relation to gender and streams of education. The subjects of the study consisted of 120 undergraduate boys and girls enrolled in the Arts, Commerce, and Science streams of education. Primary data were collected using an academic self-efficacy scale. The results revealed a significant positive relationship between the student’s academic self-efficacy and academic performance. The results also indicated a significant influence of academic self-efficacy on the academic achievement of students. Further, the results revealed that undergraduate students of the science stream were having high academic self-efficacy were having significantly higher academic performance as compared to others. The results of the study were discussed.